Flu vaccination in children. The pleasant surprise of an indirect positive effect - Gaetano Bottaro; Giuseppe Bottaro; Filippo Di Forti; Mara Nicosia (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Influence or flu is an infectious disease affecting the upper and lower respiratory tract. It has a high frequency in children, making them a specific target [1,2]. Flu is a serious public health problem and results into very high human and socio-health costs [3]. Seasonal flu epidemics are predictable and, most of all, entirely preventable through vaccination, which, over the years, has proven to be a safe and effective measure [4,5].